QUEQUE SYSTEM WITH SINGLE CHANNEL SINGLE PHASE METHOD FOR CLINIC SERVICE - Muhamad Rizqi Jamaludin; Yunus Fadhillah (Jupiter: Journal of Computer & Information Technology, 2022)
The clinic is a small-scale public health facility located in the city of Bekasi. The waiting room capacity is limited, which is a problem for patient queues. The arrival rate of patients reaches 28 people/hour and the fastest doctor's examination service is 4 minutes per patient causing doctors to serve all patients for 5.6 hours while the clinic's operating time is only 3 hours. This clinic only has one registration service and one queue, to solve this problem a single channel single phase method is used combined with web technology and notification messages to break down patient queues. The combination technology reduces the density of patient queues by up to 50% from 28 people/hour to 14 people/hour so that the waiting room capacity can be maximized and not exceed capacity.